Epistemic agency, a double-stimulation, and video-based learning: A formative intervention study in language teacher education. (February 2021) - Yang, Hongzhi
Abstract: Recent literature emphasizes the importance of viewing teachers as agents in knowledge-building practice. This study aimed to develop preservice language teachers' epistemic agency in creating their language teaching resources through a double stimulation design using video-based learning modules. The study was conducted in a secondary language teacher education program in an Australian university. The first phase of the design presented a problem in language teaching, such as how to create resources for teaching Chinese characters, as the first stimulus. The second stimuli included a short video-clip containing an experienced teachers' teaching demonstration as a resolution to the problem, group discussions, and discussion worksheets, which supported the participants to develop their own resolution to the problem in their lesson plans for teaching Chinese. The data included an initial survey results, audio-recorded group discussions, discussion worksheets, and assignment analysis. Based on the conflict of motives revealed in the initial survey, the dialogic analysis of the group discussion and content analysis of the assignment revealed the development of their epistemic agency in forming and transforming the object of learning. The findings revealed that the double stimulation design and collaborative discussions enhanced preservice teachers' epistemic agency in creating new ideas and language teaching resources.